A case of hypercalcaemia in an immunocompetent patient with Mycobacterium avium intracellulare. (June 2017) - Parsons, Christine E; Singh, Sujata; Geyer, Holly L
Mycobacterium avium intracellulare infection or colonization should be considered in the differential diagnosis of hypercalcemia, especially in immunocompromised individuals, in the appropriate clinical context.